STRATEGI HUBUNGAN MASYARAKAT DALAM MENINGKATKAN CITRA POLISI PADA KEPOLISIAN RESORT KOTA PONTIANAK - E.01107116, Wantini (FISIP Universitas Tanjungpura, 2013)
This research depict about Strategy of Public Relations of In Improving Police Image of at Police of Resort of Town Pontianak of pursuant to analysis SWOT that is Strength, Weakness, Opportunity and Threats. Related about how to improve the police image in overcoming irresponsible action by some apparatus police affecting ugly at image of police of resort of town pontianak, of course need the existence of police image conducted with the strategy of public relations internally like follow-up mistake or collision a person by giving guidance, commemoration of up to sanction gift of at the a person at police.Â Keywords : Ugly Image of Police, Police Image, Strategy of Public Relations.